OsTPR boosts the superior grains through increase in upper secondary rachis branches without incurring a grain quality penalty - Pasion, Erstelle A.; Badoni, Saurabh; Misra, Gopal; Anacleto, Roslen; Parween, Sabiha; Kohli, Ajay; Sreenivasulu, Nese (Wiley, 2021)
To address the future food security in Asia, we need to improve the genetic gain of grain yield while ensuring the consumer acceptance. This study aimed to identify novel genes influencing the number of upper secondary rachis branches (USRB) to elevate superior grains without compromising grain quality by studying the genetic variance of 310 diverse O. sativa var. indica panel using single‐ and multi‐locus genome‐wide association studies (GWAS), gene set analyses and gene regulatory network analysis. GWAS of USRB identified 230 significant (q‐value < 0.05) SNPs from chromosomes 1 and 2. GWAS targets narrowed down using gene set analyses identified large effect association on an important locus LOC_Os02g50790/LOC_Os02g50799 encoding a nuclear‐pore anchor protein (OsTPR). The superior haplotype derived from non‐synonymous SNPs identified in OsTPR was specifically associated with increase in USRB with superior grains being low chalk. Through haplotype mining, we further demonstrated the synergy of offering added yield advantage due to superior allele of OsTPR in elite materials with low glycaemic index (GI) property. We further validated the importance of OsTPR using recombinant inbred lines (RILs) population by introgressing a superior allele of OsTPR into elite materials resulted in raise in productivity in high amylose background. This confirmed a critical role for OsTPR in influencing yield while maintaining grain and nutritional quality.